Effect of Fe on Jahn-Teller distortion and magnetic transitions in GdMn1-xFexO3 (x= 0.3 and 0.5) - Tiwari P.; Rath C. (My University, 2025)
In this report, the structure and the rich sequence of magnetic transitions in GdMnO3 nanoparticles synthesized through sol-gel technique have been studied after incorporating of 30 and 50 at% of Fe. GdMn1-xFexO3 (x = 0.3 and 0.5) demonstrate pure phase with orthorhombic structure Pbnm space group. Rietveld refinement of X-ray powder diffraction data reveals that with increase in Fe concentration O′ type orthorhombic structure converted to O type orthorhombic one. The decrease in volume is attributed to the dominating Mn4+ ions more than that of Fe2+ ions which is confirmed from XPS analysis. With increase in Fe doping temperature dependent magnetization shows an increase in TN from ∼210 K at x = 0.3and ∼280 K at x = 0.5 which is much higher than pure GdMnO3, (TN ~42 K). Fe doping also affect the magnetic transitions at ∼11 and ∼5 K observed in GdMnO3 significantly. © 2019 Elsevier B.V.